TEACHING PRAGMATIC COMPETENCE IN THE CONTEXT OF USING SPEECH ACTS - Shamsutdinova Lyutsiya Rafailovna (Western European Studies, 2024)
This article explores teaching pragmatic competence in the context of using speech acts "Request" and "Advice". Considering the significance of context for language understanding and use, the author proposes an approach based on the analysis of authentic video materials for situational learning. The article presents the methodology and research findings, emphasizing the importance of integrating pragmatic skills into language instruction using realistic situations from the real world.
Keywords: linguistic competence; pragmatic competence; speech act